Biosynthesis Of Poly(3-hydroxybutyrate) By Cupriaviadus Necator Dsm 428 Utilizing Waste Date Fruits As A Carbon Source - Nur Aqilah Abdul Wahab, Siti (Pusat Pengajian Teknologi Industri, 2020)
Many researches have been conducted to find a replacement for conventional petroleumderived plastics. Poly(3-hydroxybutyrate) (PHB) is biodegradable polymers produced from a renewable source have gained many interest to replace conventional plastic, as it possesses excellent chemical and physical properties, with an advantages of complete biodegradability. The limitation in producing huge amount of PHB is due to its expensive cost of carbon sources. This study focus on the production of PHB by Cupriavidus necator using low-cost carbon sources such as waste of date fruits. Three concentration ratios of date fruits to water was prepared which are 1:3, 1:5, and 1:8 with the fermentation condition of 30℃, 200 rpm and up to 29 hours of fermentation. Analysis of sugar content in date fruits solution was performed prior and after the fermentation process. Glucose content shows the highest amount compared to fructose and sucrose which are 48.5 ± 6.3%, 55.7 ± 3.8% and 60.6 ± 5.1%. The average CDW of ratio 1:3, 1:5 and 1:8 are 0.179 ± 0.03g/L, 0.166 ± 0.01g/L and 0.180 ± 0.01g/L. While the PHB content are, 7.9± 3.0%, 4.1± 3.4% and 10.4± 9.6% respectively. Ratio 1:8 state the highest CDW and PHB in comparison to all ratios even it is the most diluted date fruits solution. This observation is due to effective utilization of carbon sources as it contained the highest glucose compared to other ratios, and limited amount of nitrogen (1.45 ± 1.06%) which enhanced the positive effect on PHB production.